Preferência de Atta sexdens (Hymenoptera, Formicidae) por folhas de eucalipto imersas em diferentes concentrações de solução de extrato de Ipomoea batatas (Convolvulaceae) - Mercadante, Maria Eugênia Gobbo (Universidade Federal de São Carlos, 2019)
The use of plant extracts in agriculture can be an alternative for controlling leaf-cutting ants in agroecosystems, providing greater autonomy for farmers and avoiding environmental pollution with residues, unlike conventional methods that are costly and leave a high residual rate in the environment. This study aimed to evaluate the preference of Atta sexdens (Linnaeus, 1758) worker ants for eucalyptus leaf disks (Eucalyptus grandis) immersed in different concentrations of sweet potato extract solution (Ipomoea batatas). For field bioassays, three distinct foraging trails from adult nests of A. sexdens were selected. Three extract concentrations were used: C5 (5 mg/ml), C50 (50 mg/ml), C100 (100 mg/ml), in addition to the control treatment (Absolute Ethanol). In each trail, 10 eucalyptus leaf disks immersed in their respective treatments (extracts) were offered per bioassay. The duration of each bioassay was 15 minutes, totaling 12 repetitions and 180 minutes of evaluation per trail. Air relative humidity (RH) and temperature were also measured. The number of carried disks per treatment/repetition was counted, with no significant difference between sweet potato extract concentrations (p > 0.05). It is worth noting that further studies should be conducted to assess the non-repellency of sweet potato extracts at the concentrations used.
Preference of Atta sexdens (Hymenoptera, Formicidae) for eucalyptus leaves immersed in different concentrations of Ipomoea batatas (Convolvulaceae) extract solution
Keywords: Formigas-cortadeiras; Bioensaios; Discos carregados; Batata-doce; Leaf-cutting ants; Bioassays; Loaded discs; Sweet potato; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE